2017
DOI: 10.1111/ffe.12732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic nanocrystal surface modification on residual stress and fatigue cracking in engineering alloys

Abstract: The effects of ultrasonic nanocrystal surface modification (UNSM) on residual stresses and fatigue crack initiation were investigated in various engineering alloys. It was found that higher contact force and smaller pin in UNSM produced higher compressive residual stresses at the surface and subsurface of the alloys. The compressive residual stresses were found to be higher in high yield strength alloys. A deeper compressive residual stress field was observed in alloys with higher elastic modulus and strain ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…An increase in the static load results in a deeper valley-depth as follows: 9.0 μm for 10 N, 11.1 μm for 30 N, and 11.2 μm for 50 N specimens. It suggested that valley depth may be associated with the intrinsic mechanical properties, such as yield strength and elastic modulus [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the static load results in a deeper valley-depth as follows: 9.0 μm for 10 N, 11.1 μm for 30 N, and 11.2 μm for 50 N specimens. It suggested that valley depth may be associated with the intrinsic mechanical properties, such as yield strength and elastic modulus [21].…”
Section: Resultsmentioning
confidence: 99%
“…The plastic deformation produces a 1–2 mm deep compressive residual stress field in the material. The combination of surface deformation, the nanostructured layer, and compressive residual stresses causes a delay in fatigue crack initiation [21].…”
Section: Introductionmentioning
confidence: 99%
“…This difference is due to the different number of strikes. It is well established that the induced compressive residual stress is the most crucial property, which determines the strength and fatigue lifespan of a material [ 35 , 36 ]. It was also reported earlier that SP and USP processes induces high compressive residual stress in the surface layer thanks to the severe plastically deformed layer [ 11 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…After calculation, we consider SSF ¼ 1:96 as the theoretical stress concentration factor of bolted joints. The crack propagation life of bolted joints at different test temperatures and stresses 37,38 are obtained by substituting related parameters into equation (20). The theoretical fatigue life of 2024 aluminum alloy joints are compared with the experimental data, 10 as shown in Table 6.…”
Section: Fatigue Life Analysis Of Plane Bolted Jointsmentioning
confidence: 99%